2000
DOI: 10.1073/pnas.110138997
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of huntingtin fibrillogenesis by specific antibodies and small molecules: Implications for Huntington's disease therapy

Abstract: The accumulation of insoluble protein aggregates in intra and perinuclear inclusions is a hallmark of Huntington's disease (HD) and related glutamine-repeat disorders. A central question is whether protein aggregation plays a direct role in the pathogenesis of these neurodegenerative diseases. Here we show by using a filter retardation assay that the mAb 1C2, which specifically recognizes the elongated polyglutamine (polyQ) stretch in huntingtin, and the chemical compounds Congo red, thioflavine S, chrysamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
191
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(203 citation statements)
references
References 26 publications
10
191
1
1
Order By: Relevance
“…Therefore, despite their well-established role as modulators of protein misfolding and consequent aggregation, overexpression of HSPs may delay polyglutamine toxicity only up to a certain level, which may depend on the level of expression of the mutant protein, the size of the polyglutamine tract and the protein context in which it is expressed. Another study also reported the beneficial effects of Congo red, an azo-dye that binds preferentially to β-sheets containing amyloid fibrils and can specifically inhibit oligomerization (Klunk et al, 1989;Heiser et al, 2000). Congo red administration, either i.p.…”
Section: 3mentioning
confidence: 96%
“…Therefore, despite their well-established role as modulators of protein misfolding and consequent aggregation, overexpression of HSPs may delay polyglutamine toxicity only up to a certain level, which may depend on the level of expression of the mutant protein, the size of the polyglutamine tract and the protein context in which it is expressed. Another study also reported the beneficial effects of Congo red, an azo-dye that binds preferentially to β-sheets containing amyloid fibrils and can specifically inhibit oligomerization (Klunk et al, 1989;Heiser et al, 2000). Congo red administration, either i.p.…”
Section: 3mentioning
confidence: 96%
“…Large screening campaigns have led to the identification of a variety of compounds that directly interfere with Aß, mHtt and Tau protein misfolding and aggregation in cell-free systems, as well as compounds that modulate the activity of heat-shock proteins and other chaperones [132][133][134][135][136][137][138] (Figure 4). However, for both classes of compounds, the translation of therapeutic efficacy into mouse models has been difficult.…”
Section: Targeting Protein Misfolding Directly And/or Through Chaperonesmentioning
confidence: 99%
“…While early studies focused on preventing the formation of large amyloid aggregates, it is now clear that misfolding events occurring early in the amyloidogenic process lead to the generation of monomers or small oligomers that can mediate neurotoxicity and degradation 142,143 . Due to difficulties in detecting these smaller toxic assemblies, the exact mechanism of action for many aggregation inhibitors such as the benzothiazoles, C2-8 or triazines remains unknown, and while they prevent the formation of large Aß plaques and mHtt aggregates 132,133,136 , they might not interfere with initial misfolding steps and thus not have a significant impact on pathogenesis (Figure 4).…”
Section: Targeting Protein Misfolding Directly And/or Through Chaperonesmentioning
confidence: 99%
“…Besides small molecule promoters of functional proteostasis, compounds that directly target the aggregation process have been identified. They include substances such as Congo red, Thioflavine S, PGL-135 or EGCG ((-)-epigallocatechin-3-gallate), which reduce the formation of polyQ-containing HTTex1 aggregates [41][42][43]. To date, the mode of action of EGCG has been studied most extensively (Fig.…”
Section: Identification Of Small Molecules That Influence Polyq-mediamentioning
confidence: 99%